1995
DOI: 10.1021/bi00001a001
|View full text |Cite
|
Sign up to set email alerts
|

Site-Directed Isotope Labeling and ATR-FTIR Difference Spectroscopy of Bacteriorhodopsin: The Peptide Carbonyl Group of Tyr 185 Is Structurally Active During the bR .fwdarw. N Transition

Abstract: The largest secondary structural change occurs in the bacteriorhodopsin (bR) photocycle during the M-->N transition. In this work site-directed isotope labeling (SDIL) and attenuated total reflection Fourier transform infrared (ATR-FTIR) difference spectroscopy were used to investigate this conformational change. L-Tyrosine containing a 13C isotope at the carbonyl carbon was selectively incorporated at Tyr 57, Tyr 147, and Tyr 185 by SDIL. This involves the cell-free expression of bR in the presence of Escheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 45 publications
5
70
0
Order By: Relevance
“…Similar results are also obtained from low temperature steady-state measurements, where the N intermediate is stabilized by either high pH or low temperature (16,18). In a recent study combining attenuated total reflection (ATR) FTIR difference spectroscopy and sitedirected isotope labeling (SDIL), it was found that part of the M 3 N transition involves the Tyr-185/Pro-186 region of the F-helix (19). This region may function as a hinge which allows reorientation of the F-helix.…”
Section: Bacteriorhodopsin (Br)supporting
confidence: 70%
“…Similar results are also obtained from low temperature steady-state measurements, where the N intermediate is stabilized by either high pH or low temperature (16,18). In a recent study combining attenuated total reflection (ATR) FTIR difference spectroscopy and sitedirected isotope labeling (SDIL), it was found that part of the M 3 N transition involves the Tyr-185/Pro-186 region of the F-helix (19). This region may function as a hinge which allows reorientation of the F-helix.…”
Section: Bacteriorhodopsin (Br)supporting
confidence: 70%
“…Further progress should be possible by combining FTIR with methods of band assignment including isotope labeling and site-directed mutagenesis. In addition, it should be possible to apply specialized FTIR techniques including polarization (40,58) and attenuated total reflection (52) to probe changes in orientation of specific groups under well defined aqueous environment.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies based on tyrosine isotope labels (41), site-directed mutagenesis (21), and site-directed isotope labeling (58) concluded that tyrosine bands identified in the FTIR difference spectra of bacteriorhodopsin arose from protonation changes in Tyr-185 located in the F-helix. Subsequent FTIR measurements on bR containing a 13 C isotope label in the C1 position of Tyr-185 indicated that the Tyr-185/Pro-186 peptide bond buried in the center of the F-helix undergoes some type of structural rearrangement (59). An interesting possibility is that the Tyr-185/Pro-186 bond serves as a hinge, which gives rise to the apparent tilting of the F-helix late in the bR photocycle (60,61).…”
Section: Figurementioning
confidence: 99%